2008
DOI: 10.1128/aac.00011-08
|View full text |Cite
|
Sign up to set email alerts
|

A Morpholino Oligomer Targeting Highly Conserved Internal Ribosome Entry Site Sequence Is Able To Inhibit Multiple Species of Picornavirus

Abstract: Members of the genera Enterovirus and Rhinovirus (family

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…These results suggest that CSDE1 is a universal factor for translation initiation in human enteroviruses. Stone et al (2008) reported that morpholino oligomers targeting IRES inhibited multiple species of picornaviruses. Using a similar approach targeting the IRES region, which interacts with CSDE1, potential broad therapeutic inhibitors against diverse human enteroviruses could be developed.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CSDE1 is a universal factor for translation initiation in human enteroviruses. Stone et al (2008) reported that morpholino oligomers targeting IRES inhibited multiple species of picornaviruses. Using a similar approach targeting the IRES region, which interacts with CSDE1, potential broad therapeutic inhibitors against diverse human enteroviruses could be developed.…”
Section: Discussionmentioning
confidence: 99%
“…This same double-target approach was used against several other viruses that included clinically important RSV, HSV1 (87,88), the picornavirus family (89) and influenza viruses (9092). Oligomers were targeted to the AUG sites or the highly conserved terminal sequence of appropriate genes.…”
Section: Rna-blocking Oligonucleotides For Other Indicationsmentioning
confidence: 99%
“…These arginine-based peptides with the 6-aminohexanoicspaced oligoarginine (R-Ahx-R)4 have successfully delivered Morpholinos to the nucleus and cytosol in vitro (11) and in vivo (12), including sustained induction of dystrophin expression in mdx mice (13). They have also been shown to actively or prophy-lactically knock down viral titers in various tissues of mice infected with corona virus (14), picornavirus (15), respiratory syncytial virus (16), and influenza A (17). However, it should be noted that arginine-based peptides are not generally available to the research community and that their greatest successes have been in delivering Morpholinos to the cytosol of what would be considered easily deliverable tissues like liver (18) or leaky muscle (19).…”
Section: Introductionmentioning
confidence: 99%